2002
DOI: 10.1136/jnnp.73.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Detection of preclinical motor neurone loss in SOD1 mutation carriers using motor unit number estimation

Abstract: Objective: To determine the pattern of motor neurone loss in amyotrophic lateral sclerosis (ALS). In particular, to determine whether there is a gradual life long presymptomatic motor neurone loss or, alternatively, a sudden catastrophic loss just before the onset of symptoms. Method: The statistical motor unit number estimation (MUNE) technique was used in a longitudinal study of 19 asymptomatic carriers of the Cu, Zn superoxide dismutase 1 (SOD1) gene. MUNE results were compared with those of 34 age and sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 10 publications
4
73
1
2
Order By: Relevance
“…24 Studies in presymptomatic patients with mutations of the superoxide dismutase-1 gene suggest that cortical excitability, 25 as well as LMN loss, 26 is an early event associated with the development of symptoms.…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 99%
“…24 Studies in presymptomatic patients with mutations of the superoxide dismutase-1 gene suggest that cortical excitability, 25 as well as LMN loss, 26 is an early event associated with the development of symptoms.…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 99%
“…At presymptomatic time points (i.e., weeks 9-12), focal activation occurs for PNS macrophages and spinal cord microglia. Following clinical onset (i.e., weeks [12][13][14][15][16][17][18][19], activation of innate immunity becomes widespread in both tissues as indicated by FACS and histological analysis.…”
Section: Macrophage Activation Occurs Throughout the Peripheral Nervousmentioning
confidence: 99%
“…Degeneration of motor axons in the periphery is an early and significant pathological feature in ALS patients and mutant SOD1 mice (11,12). Mutant SOD1 also induces defects in peripheral axon transport, which may be a primary determinant of motor neuron death (13).…”
mentioning
confidence: 99%
“…1 Limited data from a number of healthy individuals at risk for ALS by virtue of their carrying a mutation in the SOD1 gene (SOD1ϩ) suggest a decline in motor unit numbers several months in advance of the appearance of symptoms. 2 Similarly, limited threshold tracking transcranial magnetic stimulation data from 3 presymptomatic SOD1ϩ individuals suggests an increase in cortical excitability within 3 months prior to the onset of symptoms. 3 Finally, a single prior study of 8 presymptomatic SOD1 mutation carriers reported decreased fractional anisotropy, increased tensor trace, and increased radial diffusivity in the posterior limb of the internal capsule.…”
mentioning
confidence: 99%